Pendampingan Konsultasi Investasi Melalui Klinik Saham di Pondok Pesantren Monash Institute - Bahri, Saiful; Bahri, Maskudi; Karsiati; Purwanggono, Cuk Jaka; Purnomo, Suseno Hadi (Perigel: Jurnal Penyuluhan Masyarakat Indonesia, 2024)
Investment activities in the capital market are increasingly popular among various groups, including students (santri) at Islamic boarding schools (Pesantren). However, understanding of stock investment remains limited among these students. To address this need, we organized a community service activity in the form of a stock investment consultation clinic at Monash Institute Islamic Boarding School. The aim of this activity is to provide an understanding of stock investment, improve financial literacy, and help students apply safe and effective investment strategies. This activity involves training, discussions, and direct consultations with investment experts. The results of the activity showed an increase in the students' knowledge of financial literacy and their awareness of investment in the capital market